Spermatogenesis after extreme hyperthermal, hypothermal and traumatic infl uences and the possibility of its drug correction in the experiment - N. V. Avramenko; O. A. Nikiforov; О. О. Lomeyko (Zaporožskij Medicinskij Žurnal)
Introduction